How Probiotics Affect the Microbiota - Wieërs, Grégoire; Belkhir, Leila; Enaud, Raphaël; Leclercq, Sophie; Philippart de Foy, Jean-Michel; Dequenne, Isabelle; de Timary, Philippe; Cani, Patrice D. (Frontiers in Cellular and Infection Microbiology, 2020)
Probiotics have been used to treat a variety of diseases for decades: however, what is the rationale under this? Such a treatment was first proposed in the early 19th century based on observations of decreased Bifidobacteria populations in children suffering diarrhea, suggesting that oral intake of Bifidobacteria could replete microbiota in a subpopulation and improve health. Since then, studies have shown modifications in gut or skin microbiota in the course of a variety of diseases and suggested positive effects of certain probiotics. Most studies failed to report any impact on the microbiota. The impact of probiotics, as well as of bacteria colonizing food, does not reside in their ability to graft in the microbiota but rather in sharing genes and metabolites, supporting challenged microbiota, and by direct influence on epithelial and immune cells. Such observations argue that probiotics could be associated to conventional drugs for insulin resistance, infectious diseases, inflammatory diseases and psychiatric disorders and could also interfere with drug metabolism. Nevertheless, in the context of a plethora of probiotic strains and associations, produced in such conditions that do not allow direct comparisons, it remains difficult to know whether a patient would benefit from taking a particular probiotic. In other words, although several mechanisms are observed when studying a single probiotic strain, not all individual strains are expected to share the same effects. In order to clarify the role of probiotics in clinics, we explore here the relation between probiotic gut and skin microbiota.